Effects of forefoot bending stiffness of badminton shoes on agility, comfort perception and lower leg kinematics during typical badminton movements - Park, S.-K.; Lam, W.-K.; Yoon, S.; Lee, K.-K-; Ryu, J. (Sports Biomechanics, 2017)
This study investigated whether an increase in the forefoot bending stiffness of a badminton shoe would positively affect agility, comfort and biomechanical variables during badminton-specific movements. Three shoe conditions with identical shoe upper and sole designs with different bending stiffness (Flexible, Regular and Stiff) were used. Elite male badminton players completed an agility test on a standard badminton court involving consecutive lunges in six directions, a comfort test performed by a pair of participants conducting a game-like practice trial and a biomechanics test involving a random assignment of consecutive right forward lunges. No significant differences were found in agility time and biomechanical variables among the three shoes. The players wearing the shoe with a flexible forefoot outsole demonstrated a decreased perception of comfort in the forefoot cushion compared to regular and stiffer conditions during the comfort test (p<0.05). The results suggested that the modification of forefoot bending stiffness would influence individual perception of comfort but would not influence performance and lower extremity kinematics during the tested badminton-specific tasks. It was concluded that an optimisation of forefoot structure and materials in badminton shoes should consider the individuals perception to maximise footwear comfort in performance. ABSTRACT FROM AUTHOR